Single CCCCTA-based SITO biquad filter with electronic tuning - Singh S.V.; Maheshwari S.; Chauhan D.S. (My University, 2025)
In this paper a new single-input three-output (SITO) electronically tunable voltage-mode biquad filter using single current controlled current conveyor trans-conductance amplifier (CCCCTA) is proposed. The proposed voltage-mode filter employs only one resistor and two grounded capacitors as passive elements and can simultaneously realize low pass (LP), band pass (BP), and band reject (BR) filter functions. The circuit possesses low active and passive sensitivity. The effects of parasitic and non-idealities are also considered. PSPICE simulation results are included for verification of proposed circuit. © 2011 IEEE.